Perspectivas para educação contra a barbárie: um olhar crítico-filosófico à intervenção assistida por animais em ambiente escolar - Munhoz, Fabiane Bortoluzzi Angelo (2022)
This thesis is part of the Line 1 Research – Teaching, Knowledge and Professional Development, of the Education Graduate Program (PPGE), at Universidade Federal de Santa Maria (UFSM). The research addresses Animal Assisted Intervention (AAI) in the school environment as a possible perspective capable of contributing to education against barbarism. The approach used for the study follows the perspective of qualitative research, with a theoretical axis in the contributions of the Frankfurt School Critical Theory, especially in the understanding of Theodor Adorno and Max Horkheimer. The study is philosophically based on the diagnosis of the times made by Adorno and Horkheimer in the work "Dialectics of Enlightenment" with the education against barbarism as the horizon. The instruments used were the literature review and the semi-structured interviews with specialists to generate data. The chapters presuppose the guarantee of One Health and One Welfare, two dear concepts to the AAI and considered pillars of good practices in Animal Assisted Intervention (AAI). Initially, we launched a critical philosophical look in order to discuss the main issue that motivated our study, which centers on two aspects: the awareness of the necessary attention to the well-being of all those involved in an AAI program in the school environment and the didactic comprehension of the dog's role in AAI, which we propose as an incremental resource, as it is a thesis in the Educational field, an intellectual space conducive to proposals for comprehending the identified gaps. Still, with the intention of collaborating to raise awareness about the introduction of dogs in the school environment in AAI programs, a protocol elaborated from the experience of the interviewee and the researcher was proposed. Therefore, we consider to be possible the perception of Animal Assisted Interventions (IAAs) as a perspective against barbarism, and we use the allegory Aletheia for its contextualization.